Implementasi Design Thinking Untuk Pengembangan Aplikasi Website Daily Checkpoint Motion Designer Dengan Framework Laravel - Feliana Amara Pasha (CV. Multi Kreasi Media, 2023)
The essence of the design activity is thinking about ways that whatever we design can better meet the needs of its users. Therefore, the innovation process that uses the design thinking approach method can be said to be Human Centered Design. Because the focus is indeed helping the user or human to solve their problems and achieve what they aspire to. This is what makes it very suitable to answer the problems and constraints that exist in the Motion Designer team at PT. Ruang Raya Indonesia so that it becomes easier to consider in visualizing, specifying, building, and documenting a software development system.